2022
DOI: 10.1111/jpy.13293
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Host Specificity and Temperature on Bacterial Communities Associated with Sargassum (Phaeophyceae) Species

Abstract: Host-related microbiota are critically important for the adaptation/acclimation of hosts to changing environments, but how environmental factors and host characteristics shape the microbial communities remains largely unknown. We investigated the effects of temperature on habitat-forming macroalgae and their associated bacterial communities. Three Sargassum species (S. horneri, S. fusiforme, and S. thunbergii) and seawater samples were sampled in Gouqi Island, China, and these macroalgal samples were incubated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Previous studies have reported species, morphology and biogeography as sources of microbial variations in holopelagic Sargassum species [16,17,61]. However it is unlikely that the environmental water column microbiome itself could affect our results, since water and macroalgal microbiomes are shown to differ greatly [16,22,62].…”
Section: Highmentioning
confidence: 68%
“…Previous studies have reported species, morphology and biogeography as sources of microbial variations in holopelagic Sargassum species [16,17,61]. However it is unlikely that the environmental water column microbiome itself could affect our results, since water and macroalgal microbiomes are shown to differ greatly [16,22,62].…”
Section: Highmentioning
confidence: 68%
“…Interestingly, these groups were not isolated through cultivation efforts. While previous studies on macroalgae microbiome have reported that both Gram‐negative and Gram‐positive communities exhibit host‐specificity (Kuba et al, 2021; Li et al, 2022; Sanders‐Smith et al, 2020), they have also highlighted that the structure of bacterial communities is more likely associated with functional genes rather than taxonomy (Morrissey et al, 2019; Roth‐Schulze et al, 2018). Though we have detected a higher abundance of Actinomycetota in C. crispus (Figure 6), the most representative groups within this phylum were the same in both macroalgae.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al. (2022) found that community composition of bacterial epiphytes on rooted Sargassum species varied with host species and, to a lesser extent, temperature. Additionally, phnP genes were enriched by amendments of vitamins and methanol similar to amendments of HMWDOM (Gifford et al., 2016), indicating additional factors influencing MPn apart from phosphate availability.…”
Section: Resultsmentioning
confidence: 99%
“…Contributions from other macroalgal species, or even biogeographic and temporal effects acting on Sargassum, may drive additional flux, and we further note that the highest observed production rate (for D. baillouviana) was ∼14-fold greater than the rate used for these calculations. Li et al (2022) found that community composition of bacterial epiphytes on rooted Sargassum species varied with host species and, to a lesser extent, temperature. Additionally, phnP genes were enriched by amendments of vitamins and methanol similar to amendments of HMWDOM (Gifford et al, 2016), indicating additional factors influencing MPn apart from phosphate availability.…”
Section: Mpn Lysis As a Source Of Phosphorus And Atmospheric Methanementioning
confidence: 96%